Effect of weight-control practices of high-level female judokas over competition period on body composition and factors of performance - Gallot, M.; Zorgati, H.; Prieur, F.; Rebot-Vibarel, N.; Collomp, K.; Rieth, N. (Science & Sports, 2019)
Purpose: This study was conducted to estimate the impact of the food practices of high-level judokas on body composition, muscle performance and food habits. Methods: Thirteen elite judokas were distributed in two groups: a group with weight-control practice (group D, n=6) and a group without it (group ND, n=7). Eating habits, sport performance and body composition were evaluated three times during the experiment: out (ES), pre (PREC) and post-competitive (POSTC) periods. Results: For the D group, we observed a decrease of body mass index, of the sum of skin folds thickness and of circumference of thigh between ES and PRE C periods, and an increase between PRE C and POST C periods. For the ND group, no difference was observed whatever the considered period. For strength tests, there is no difference between groups and between the different periods. Total energy intake and macronutrient intake of the D group decreased between ES and PRE C periods. This decrease concerned mainly fat intake. These parameters increased between PRE and POST C periods. Conclusion: In this study carried out on elite female judoka, changes in body composition and total energy intake had no effect on muscle performance and did not cause eating disorders.